THE HAPPINESS ANALYSIS OF PEOPLE LIVING WITH HIV AIDS (PLWHA) IN DENPASAR CITY - Pardita D.P.Y.; Bendesa I K.G.; Sudibia I K.; Saskara I.A.N. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
HIV AIDS is a disease caused by a virus that has not been cured until now. HIV AIDS was expected to reduce the life expectancy of PLWHA so that the expected contribution of PLWHA in the economic sector and social development becomes smaller. Another result of HIV AIDS in the environment is the imposition of social penalties for PLWHA, such as acts of avoidance, exile, rejection, and discrimination. In addition, PLWHA can’t do their jobs optimally or even have to lose their jobs because of poor physical condition, so they can lose income. Social, economic, psychological and environmental problems for PLWHA are feared to reduce the quality of life for PLWHA which will have an impact on the happiness of PLWHA themselves. This study aims to find the condition of PLWHA happiness, the difference between happiness of PLWHA with male and female, the influence of socio-economic factors, psychological factors, and environmental factors on religiosity, as well as the influence of socio-economic factors, psychological factors, environmental factors, and religiosity on PLWHA happiness in Denpasar City. The data used in this study were primary data obtained by observation, structured interviews, and in-depth interviews. The sample used was 148 PLWHA respondents in Denpasar City using the Consecutive Sampling methods. The data obtained then analyzed using the Structural Equation Modeling (SEM) method through the Partial Least Square (PLS) application program. The results of this study are PLWHA in Denpasar City who are predominantly still feeling happy can be interpreted that HIV AIDS does not necessarily eliminate the hope of PLWHA to live happily, while gender does not have a relationship with the happiness level of PLWHA in Denpasar City. Socio-economic factors and environmental factors have a positive and significant effect on the religiosity of PLWHA in Denpasar City, while psychological factors don’t affect the religiosity of PLWHA in Denpasar City. Socio-economic factors, psychological factors, and environmental factors do not affect the happiness of PLWHA in Denpasar City directly, but religiosity has a positive and significant effect on the happiness of PLWHA in Denpasar City. It can be said that religiosity mediates in full the relationship between socio-economic factors and environmental factors with the happiness of PLWHA in Denpasar City, while on the other hand religiosity does not mediate the relationship between psychological factors and the happiness of PLWHA in Denpasar City. The happiness of PLWHA in Denpasar City is influenced by its religiosity. PLWHA, who have faith in God, have knowledge about the religion they embrace, and practice the teachings of religion well and can truly feel happiness in their lives. Government policy through socialization and lectures by presenting religious leaders is expected to provide motivation and instil religious values to PLWHA.